2015
DOI: 10.1002/micr.22513
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar fusion with iliac bone free flap after a recalcitrant nonunion: Report of two cases

Abstract: Fractures of the calcaneus are associated with secondary osteoarthritis of the subtalar joint. In a persistent nonunion, vascularized bone flaps offer superior biologic and mechanical properties as well as accelerates joint fusion and decreases morbidity. In this report, we present results of the use of vascularized iliac bone free flap for treating subtalar failed fusions in two patients. Two patients sustained calcaneal fractures due to foot trauma, which were initially or subsequently treated with subtalar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…14 For patients with subtalar nonunions, some experts have used an iliac bone free flap to realize radiographic bony union with no recurrence of infection or wound healing problems. 15 Niedhart et al. 16 reported that an autogenous iliac graft was the gold standard clinical bone graft for subtalar joint fusion but that it may lead to donor site complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 For patients with subtalar nonunions, some experts have used an iliac bone free flap to realize radiographic bony union with no recurrence of infection or wound healing problems. 15 Niedhart et al. 16 reported that an autogenous iliac graft was the gold standard clinical bone graft for subtalar joint fusion but that it may lead to donor site complications.…”
Section: Discussionmentioning
confidence: 99%
“…14 For patients with subtalar nonunions, some experts have used an iliac bone free flap to realize radiographic bony union with no recurrence of infection or wound healing problems. 15 Niedhart et al 16 reported that an autogenous iliac graft was the gold standard clinical bone graft for subtalar joint fusion but that it may lead to donor site complications. Whether by traditional surgery, arthroscopic surgery, or other methods of minimally invasive surgery, most patients underwent autogenous iliac grafting procedures that increased the trauma, intraoperative bleeding, and risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…The iliac crest has been proven to provide bone material up to 24 cm in length and 4 cm in width, being superior compared with the fibula. 31,32 However, vascularized bone grafts over 12 cm in size should not be raised due to the increased risk of donor-site stress fractures. 33 In the present series, the widest graft was 4.5 cm in size, whereas the maximum graft length was 10 cm.…”
Section: Discussionmentioning
confidence: 99%
“…O tabagismo, além de ser reconhecido como um dos maiores problemas econômicos de saúde pública no mundo, possui efeitos negativos reconhecidos em diversos resultados pós-cirúrgicos, como complicações com ferida operatória, maiores taxas de não consolidação e piores resultados em artroplastias (6)(7)(8)(9) . O enxerto ósseo é um componente importante das artrodeses do pé e tornozelo, tendo sido muito utilizado nas décadas finais do século passado, não sendo necessário na ausência de fatores complicadores (10) . É utilizado como osteoindutor e para melhorar o potencial osteogênico em condições em que, sabidamente, o sistema biológico não é favorável, em cirurgias de revisão após a não fusão e quando permanece um grande defeito estrutural após a cruentização da articulação (11) .…”
Section: Introductionunclassified